FALL PREVENTION IN OLDER ADULTS: EFFECTIVE STRATEGIES (REMUNOM, 2025)
Considering that falls among older adults represent a growing publichealth issue, with a direct impact on autonomy, quality of life, and theburden on healthcare services, this study aims to analyze the role ofnursing in implementing preventive strategies aimed at reducing theseevents. To achieve this, an integrative literature review was conducted, with searches in databases such as SciELO and the Virtual Health Library (BVS), using controlled descriptors in Portuguese and English, coveringpublications from 2019 to 2024. Studies were included that addressednursing interventions in individuals aged 60 or older, focusing onmobility, balance, muscle strength, and functional capacity. The findingsshow that the most effective interventions involve multifactorial actions, such as strengthening exercises, environmental adaptations, healtheducation, and the use of fall risk assessment scales. Nursing care wasrelevant in both hospital and home settings, with emphasis onindividualized assessment, continuous supervision, and caregiverguidance. Initial conclusions suggest that well-structured and evidence-based nursing practices significantly contribute to fall prevention amongolder adults and promote safer and more functional aging.